2018
DOI: 10.2967/jnumed.117.203539
|View full text |Cite
|
Sign up to set email alerts
|

Targeted α-Therapy of Metastatic Castration-Resistant Prostate Cancer with 225Ac-PSMA-617: Swimmer-Plot Analysis Suggests Efficacy Regarding Duration of Tumor Control

Abstract: The aim of this evaluation was to identify the first indicators of efficacy for Ac-labeled prostate-specific membrane antigen (PSMA)-617 therapy in a retrospectively analyzed group of patients. Forty patients with metastatic castration-resistant prostate cancer were selected for treatment with three 100 kBq/kg cycles of Ac-PSMA-617 at 2-mo intervals. Prostate-specific antigen (PSA) and blood cell count were measured every 4 wk. PSMA PET/CT or PSMA SPECT/CT were used for baseline staging and imaging follow-up a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
343
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 364 publications
(357 citation statements)
references
References 38 publications
7
343
1
6
Order By: Relevance
“…It has already been demonstrated that RLT with PSMA‐617 labelled with the alpha emitter 225 Ac ( t 1/2 ≈9.9 days) may overcome this radioresistance . Recent clinical studies have reported that targeted alpha therapy (TAT) using 225 Ac‐ and 213 Bi‐labelled PSMA ligands is a promising treatment of mCRPC . Despite the great efficacy, their limited supply, the toxicity in salivary glands of 225 Ac, and the short half‐life of 213 Bi ( t 1/2 ≈46 minutes) warrant to explore other alpha‐emitting radionuclides for PSMA‐RLT.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been demonstrated that RLT with PSMA‐617 labelled with the alpha emitter 225 Ac ( t 1/2 ≈9.9 days) may overcome this radioresistance . Recent clinical studies have reported that targeted alpha therapy (TAT) using 225 Ac‐ and 213 Bi‐labelled PSMA ligands is a promising treatment of mCRPC . Despite the great efficacy, their limited supply, the toxicity in salivary glands of 225 Ac, and the short half‐life of 213 Bi ( t 1/2 ≈46 minutes) warrant to explore other alpha‐emitting radionuclides for PSMA‐RLT.…”
Section: Introductionmentioning
confidence: 99%
“…225 Ac has so far been used in conjunction with specific carrier molecules to target leukemia, glioma, neuroendocrine tumors, as well as prostate cancer . A summary of the clinical experience obtained to date is given in Table .…”
Section: Clinical Experience With 213bi and 225acmentioning
confidence: 99%
“…A summary of the clinical experience obtained to date is given in Table . The clinical tests in previous studies were carried out with 225 Ac produced, quality‐controlled, and supplied by JRC Karlsruhe.…”
Section: Clinical Experience With 213bi and 225acmentioning
confidence: 99%
See 2 more Smart Citations